Membangun UMKM yang Berkelanjutan: Kunci Mewujudkan Pekerjaan Layak dan Pertumbuhan Ekonomi - Asryatun Nisa Br Ginting; Cindy Alya Tantri; Ezika Aquilera Sitio; Hanifa Ayu S (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Building sustainable Micro,Small and Medium Enterprises (SaME) is a crucial aspect in realizing decent work and promoting inclusive economic growth. SaME, as the backbone of the economy, contribute significantly to job creation and increased gross domestic product (GDP). Thisresearch explores various factors that influence the sustainability of SaME, such as access to capital, technology, skills training, and infrastructure support. In the digital era and globalization, SaME need to adapt to innovation and sustainable business practices to remain competitive. The use of information and communication technology (ICT) and environmentally friendly approaches can improve their efficiency and competitiveness. Furthermore, the government’s role in creating supportivepolicies, including tax in centives, training, and market access, iscrucial. Collaboration between the public and private sectors was also identified as key in creating an ecosystem that supports SaME development. By facilitating business net works and improving access to resources, UMKM can be more competitive. The findings from this study suggest that the sustainable development of SaME not only contributes to the creation of decent jobs, but also plays a role in broader and sustainable economic growth, and strengthens a country’s economic resilience. Therefore, investment in SaME should be a priority in the sustainable economic development agenda.